Monitoramento ambulatorial da pressão arterial: variabilidade da pressão, descenso da frequência cardíaca ao sono e risco de eventos fatais na doença renal crônica - Marchi, Daniel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: More than half of the deaths in patients with chronic kidney disease (CKD) are attributed to cardiovascular disease. Blood pressure control (BP ) is considered a main strategy in reducing morbidity and mortality in chronic renal population. Ambulatory blood pressure monitoring (ABPM ) has been shown to be higher to office BP in defining prognosis and outcome in all stages of CKD. Some data of ABPM, such as blood pressure variability ( BPV ) and the attenuation of heart rate decrease (HRa) while sleeping were observed as risk factors for overall and cardiovascular mortality in hypertensive population, but no studies on CKD population who evaluated BPV and HRa decrease while sleeping measured by ABPM. The objectives of this study were to evaluate the prognostic impact of the BPV and the decrease of HR while sleeping obtained by ABPM in individuals with chronic kidney disease. Patients and methods : An observational, longitudinal and retrospective study which involved the analysis of 251 ABPM examinations in individuals with CKD at Hospital das Clinicas, Faculty of Medicine of Botucatu followed by a median of 34 months. Results: When comparing patients with fatal outcomes from cardiovascular causes and from all causes, with those who did not present outcomes, there is an age and prevalence of more advanced stages of CKD. Even after adjusting for CKD stage, age and PP in wakefulness, the lowest decrease of HRa while sleeping ( HR : 0.925 , 95% CI : 0.865 to 0.991 , p = 0.026 ) was independent predictor of cardiovascular mortality. The results showed no independent association between BPV, measured by the standard deviation of the pressure with mortality. Conclusion: BPV to ABPM did not show independent prognostic impact in multivariate analysis, however, the decrease of HRa while sleeping was a good marker of cardiovascular mortality in CKD, even after adjustment for misconfusion factors. The short follow-up time and ...

Introdução: Mais da metade das mortes em portadores de doença renal crônica (DRC) são atribuídas à doença cardiovascular. O controle da pressão arterial (PA) é considerado uma estratégia fundamental na redução da morbidade e mortalidade na população renal crônica. A monitorização ambulatorial da pressão arterial (MAPA) tem se mostrado superior à PA de consultório ao definir prognóstico e desfecho em todos os estádios da DRC. Alguns dados obtidos da MAPA ,como a variabilidade da pressão arterial (VPA) e a atenuação do descenso da frequência cardíaca (FC) ao sono, mostraram-se fatores de risco para mortalidade geral e cardiovascular na população hipertensa, porém não há estudos na população com DRC que avaliaram a VPA e o descenso da FC ao sono aferidos pela MAPA. Os objetivos deste estudo foram avaliar o impacto prognóstico da VPA e do descenso da FC ao sono obtidos pela MAPA em renais crônicos. Pacientes e métodos: Estudo longitudinal, observacional e retrospectivo que envolveu a análise de 251 exames de MAPA de indivíduos com DRC realizados no Hospital das Clínicas da Faculdade de Medicina de Botucatu seguidos pela mediana de 34 meses. Resultados: Ao comparar os pacientes que apresentaram desfechos fatais de origem cardiovascular e por todas as causas, com os que não apresentaram desfechos, nota-se idade superior e predominância de estádios mais avançados da DRC. Mesmo após ajuste para estádio da DRC, idade e PP na vigília, o menor descenso da FC ao sono (HR: 0,925 , IC 95% : 0,865 a 0,991, p=0,026) mostrou-se preditor independente de mortalidade cardiovascular. Os resultados não mostraram associação independente entre a VPA, avaliada pelo desvio padrão das pressões, com mortalidade. Conclusão: A VPA à MAPA não apresentou impacto prognóstico independente na análise múltipla, por outro lado, o descenso da FC ao sono foi um bom marcador de mortalidade cardiovascular ...
Keywords: Pressão arterial - Medição; Batimento cardíaco; Insuficiencia renal cronica; Estudos longitudinais; Pressão arterial - Measurement